Tandem-L Observation Concept - An Acquisition Scenario for the Global Scientific Mapping Machine - Bachmann, Markus; Tridon, Daniela Borla; De Zan, Francesco; Krieger, Gerhard; Zink, Manfred (EUSAR 2016, 2016)
The paper describes the acquisition scenario for the Tandem-L mission and shows how the mission serves the various scientific applications.
DLR Import::2019-04-03